Human Leukocyte Antigen Sensitization in Solid Organ Transplantation: A Primer on Terminology, Testing, and Clinical Significance for the Apheresis Practitioner. Issue 5 (7th September 2017) - Abbes, Sarah; Metjian, Ara; Gray, Alice; Martinu, Tereza; Snyder, Laurie; Chen, Dong‐feng; Ellis, Matthew; Arepally, Gowthami M.; Onwuemene, Oluwatoyosi
Abstract: The human leukocyte antigen (HLA) system is an important immunologic barrier that must be considered for successful solid organ transplantation. Formation of donor‐specific HLA antibodies in solid organ transplantation is an important cause of allograft injury and may contribute to recipient morbidity and mortality. Therapeutic plasma exchange is often requested to lower HLA antibody levels prior to or after transplantation and for management of HLA antibodies in the context of organ rejection. In this review, we summarize the current terminology, laboratory testing, and clinical significance of HLA sensitization in the solid organ transplant population. Furthermore, to illustrate applications of HLA testing in clinical practice, we summarize our own lung and kidney institutional protocols for managing HLA antibodies in the peri‐transplant setting.